A microchannel shell-and-tube absorber for ammonia-water absorption. (25th February 2021) - Chandrasekaran, Sriram; Hughes, Matthew; Kini, Girish; Garimella, Srinivas
Highlights: Shell-and-tube absorber with microscale geometric features developed. Absorption heat duties in the range of 5–15 kW demonstrated in compact package. Performance in co-current flow and counter-current flow compared. Wetted area in absorber experimentally determined. Coupled heat and mass transfer model agrees with data with an AAD of 3.4% Abstract: A shell-and-tube absorber with microscale geometric features that yields significant volumetric heat duties is investigated. A vertically-oriented baffled shell-and-tube heat exchanger with a tightly packed tube bundle is designed to serve as the absorber for a 10.5 kW nominal cooling capacity absorption chiller. The heat and mass transfer in this absorber is investigated experimentally at operating conditions spanning a wide range of working fluid and coupling fluid flow rates and ambient temperatures. An experimental facility is fabricated to closely simulate the operating conditions in an absorption refrigeration system. Absorption heat duties in the range of 5–15 kW are measured. In addition to operating the absorber in the baseline co-current flow configuration with premixed inlet, fluid ports are provided to enable operation in counter-current flow, where the dilute solution enters from the top and vapor enters from the bottom. The performance of these two flow configurations is compared. A preliminary heat and mass transfer model is developed to quantify the local temperatures, concentrations, and mass flow rates of the solution and vapor streams along the length of the absorber. The model predictions for total heat duty agree with the experimental results within 10% for almost all the data points, with an AAD of ~ 3.4%. The results of this study, along with the modeling framework, can guide further development of highly compact and efficient absorbers absorption systems.